DEVELOPMENT OF INNOVATION TECHNOLOGY OF CARROT SEED PRODUCTION - S. M. Sirota; V. A. Podorogin; L. V. Krivenkov; T. E. Shevchenko; I. T. Balashova (Овощи России)
Stavropol region is well known zone of vegetable seed production from 70th years of last century. Development seed production of main vegetable crops is connected with using of new technologies. New technological methods and its influence on the seed yield formation and on the quality of carrot seeds have been investigated in this study. The objects of the study were seeds of carrot variety Marlinka and different technological methods, including in schemes of sowing. Methods and conditions of experiments have been written in details with scheme of experiment by the study influence of sowing schemes on the seed productivity of carrot plants variety Marlinka. Years of study (2015-2017) have been characterized as drought. Seedling capacity of seeds was very small (about of 30%). Sowing with seed drill Matermacc (by the scheme of sowing: 25+20x20x20x20x20+25 sm) ensured the seedling capacity needed for survive of plants after winter. Yield of seeds was in 4-6 time higher in variant with using seed drill Matermacc and scheme of sowing 25+20x20x20x20x20+25 sm, than in variants with traditional technologies. Mass of 1000 seeds was similar under different technologies and schemes of sowing. But seedling capacity was significantly decreased under traditional technologies and using seed drill SZ-5,4.